Investigating the effect of obsessive‐compulsive disorder on clinical symptoms of temporomandibular joint disorders - Maryam‐Sadat Sadrzadeh‐Afshar; Behzad Salari; Ali shobeiri; Kimia HafeziMotlagh (Wiley, 2023)
Abstract Objectives Temporomandibular disorders (TMD) are a group of clinical conditions involving muscles of mastication, temporomandibular joint (TMJ), and related structures or both. TMD is characterized by facial pain in TMJ and muscles of mastication, limitation or deviation of jaw movement, and TMJ sounds during jaw movement and function. The highest risk of TMD prevalence is between 18 and 24 years, and a relationship is between chronic TMD and psychological disorders such as stress and depression. The knowledge of the function of this joint and those with TMD symptoms when visiting the dentist will help to provide an ideal treatment plan for the patient. Therefore, if the therapist is familiar with the various etiological factors of this disorder, he will provide better treatment, especially if the simultaneous effect of psychological factors such as stress and obsessive‐compulsive disorder (OCD) along with occlusal factors such as posterior cross‐bite, overjet, and overbite is measured, it can be a valuable guide for clinicians. Methods and Materials In this study, 385 patients were examined by DASS42 and Maudsley's test and classified into normal, with stress, and stress plus OCD groups. TMJ was examined for each of them by the TMD‐RDC test. The presence or absence of TMD was noted in their file. Results The prevalence of TMD was 20.7% in the normal group, 30.70% in the stress group, and 44.68% in the stress and OCD group. After analyzing the data by SPSS 24 and performing analysis of variance and Duncan tests, no significant difference was found between the probability of TMD in normal and stressed groups, but the stress and OCD group has a higher chance of TMD. Conclusion Although the co‐occurrence of stress and OCD is associated with the prevalence of TMD, it cannot be considered a cause of TMD.